Two-dimensional MOF-derived nanoporous Cu/Cu2O networks as catalytic membrane reactor for the continuous reduction of p-nitrophenol - Bai, Xiao-Jue; Chen, Dan; Li, Yu-Nong; Yang, Xi-Man; Zhang, Ming-Yu; Wang, Tie-Qiang; Zhang, Xue-Min; Zhang, Li-Ying; Fu, Yu; Qi, Xuan; Qi, Wei (Journal of membrane science, 2019)
A novel kind of Cu-based catalytic membrane reactor (CMR) has been developed for the efficient reduction of p-nitrophenol (p-NP) to p-aminophenol (p-AP) in a continuous flow-through system. The CMR is prepared by the composite of MOF-derived nanoporous Cu/Cu2O networks and a porous matrix of nylon film. In this process, the pre-synthesized Cu-MOF-nanosheets are deposited onto a porous nylon film via filtration, and then the composite membrane is in-situ reduced by NaBH4 in the liquid phase, producing nanoporous Cu/Cu2O networks/nylon composite membrane. Remarkably, the nanoporous Cu/Cu2O networks exhibit fluffy structure with multidimensional porosity, which shows relatively high mass transportation ability and excellent catalytic activity. Therefore, the nanoporous Cu/Cu2O networks/nylon composite membrane can work as highly efficient and stable CMR, which can continuously convert over 95% of p-NP to p-AP in an 8 h test (8 mL/min) without obvious structure change and deactivation. This new type two-dimensional MOF-derived CMR offers an effective and convenient continuous catalytic process from p-NP to p-AP, which would have a potential application in this industrial reduction reaction. [Display omitted] •Cu-MOF membrane is converted into nanoporous Cu/Cu2O networks by liquid-phase reduction method.•The nanoporous Cu/Cu2O networks exhibit relatively high mass transportation ability and stability.•The nanoporous Cu/Cu2O networks is used as an efficient catalytic membrane reactor for the continuous reduction of p-NP.